2022
DOI: 10.17478/jegys.1183220
|View full text |Cite
|
Sign up to set email alerts
|

Application of design thinking as a differentiation strategy for the education of gifted students: “City X”

Abstract: This research aims to apply the City X Project as a 6-hour workshop for gifted students and evaluate the workshop. The study group consists of 25 gifted secondary school students (13 Female, 12 Male) who continue their education at the Science and Art Center (SAC) in a city center. During the application process, gifted students were introduced to the City X project, and information regarding the design thinking method was presented. The story of City X was provided to the students via a digital presentation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
(36 reference statements)
0
1
0
1
Order By: Relevance
“…In earlier research performed in SACs, it was discovered that gifted students had high levels of educational technology self-efficacy as well as information and technology literacy skills (Bayra, 2020;Nacaroğlu, 2020). Several educational process experiences that allow gifted students to adapt to new technologies, support their higher-order thinking, and empower them to use and generate with technology may have contributed to their digital literacy abilities (Avcu & Er, 2020a, 2020bAvcu, Ayverdi, Ülker & Karakış, 2020;Ayverdi & Öz;Avcu & Ayverdi, 2022;Avcu & Yaman, 2022;Bozok, Geniş & Avcu, 2020;Çevik, 2021;Del Siegle, 2023;Önal & Önal, 2021). Following the findings of recent research, it can be concluded that gifted students acquired digital literacy, which is a 21st-century skills, through the education they received in SACs (Nacaroğlu, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier research performed in SACs, it was discovered that gifted students had high levels of educational technology self-efficacy as well as information and technology literacy skills (Bayra, 2020;Nacaroğlu, 2020). Several educational process experiences that allow gifted students to adapt to new technologies, support their higher-order thinking, and empower them to use and generate with technology may have contributed to their digital literacy abilities (Avcu & Er, 2020a, 2020bAvcu, Ayverdi, Ülker & Karakış, 2020;Ayverdi & Öz;Avcu & Ayverdi, 2022;Avcu & Yaman, 2022;Bozok, Geniş & Avcu, 2020;Çevik, 2021;Del Siegle, 2023;Önal & Önal, 2021). Following the findings of recent research, it can be concluded that gifted students acquired digital literacy, which is a 21st-century skills, through the education they received in SACs (Nacaroğlu, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…BİLSEM'lerde yürütülmüş olan önceki çalışmalarda, özel yetenekli öğrencilerin teknoloji ve tasarıma yönelik eğitim teknolojileri öz yeterlikleri ve bilgi ve teknoloji okuryazarlığı becerileri yüksek düzeyde bulunmuştur (Bayra, 2020;Nacaroğlu, 2020). Özel yetenekli öğrencilerin yeni teknolojilere uyum sağlamasına olanak tanıyan, üst düzey düşünmelerini destekleyen ve teknolojileri kullanıp teknolojiyle üretim yapmalarını sağlayan birçok öğretimsel süreci deneyimleri özel yetenekli öğrencilerin dijital okuryazarlık becerilerine katkı sağlamış olabilir (Avcu & Er, 2020a, 2020bAvcu, Ayverdi, Ülker & Karakış, 2020;Ayverdi & Öz;Avcu & Ayverdi, 2022;Avcu & Yaman, 2022;Bozok, Geniş & Avcu, 2020;Çevik ve diğerleri, 2021;Del Siegle, 2023;Önal & Önal, 2021). Güncel çalışmaların sonuçları doğrultusunda, özel yetenekli öğrencilerin 21. yüzyıl becerilerinden biri olan dijital okuryazarlık becerisini edinmesinde BİLSEM'lerde özel yetenekli öğrencilere yönelik verilen eğitimle başarıldığı yorumu yapılabilir (Nacaroğlu, 2020).…”
Section: Geniş öZetunclassified